DEVELOPING A GUIDELINE OF ENGLISH TEACHING MATERIALS BASED ON LOCAL CULTURE FOR VII GRADERS IN PASER REGENCY EAST KALIMANTAN - Yustina Fitriani (INOVISH JOURNAL, 2019)
Abstract : The aims of this study are: to identify the needs of English teaching materials based on local culture for VII graders of junior high school and to develop an appropriate guideline of English teaching materials based on local culture for VII graders of junior high school.Â  This study adopted the design of research and development proposed by Dick, Carey & Carey (2009). The first draft of the guideline was validated by experts and evaluated by English teachers through Focus Group Discussion. The studentsâ€™ responses also were needed to know their agreements toward the English materials based on local culture. The responses of the English teachers show the mean value ranging from 2.91 to 3.82, while the mean value of the students was ranging 2.94 to 3.62. It means both of mean value results categorized into â€œgoodâ€ and â€œvery goodâ€ based on interval range 2.52 to â‰¥ 3.28. It can be concluded that the English teachers agree with the developed guideline and the students agree with the English materials based on local culture.Â Keywords: needs analysis, developing a guideline of English teaching materials, local culture